Application of Uterus Manipulator in Total Abdominal Hysterectomy for Benign Diseases - Fateme Salehi; Sara Saeedi; Zeynab Amiriariya; Elham Feizabad (Tehran University of Medical Sciences, 2023)
Objective: Pelvic access is a challenging matter in abdominal hysterectomy especially in obese patients and presence of pelvic adhesions. Uterus manipulators (UM) have been used in a number of studies on laparoscopic approach to improve surgical performance. This study aimed to assess the impact of UM application on the operation time and blood loss in total abdominal hysterectomy (TAH) for benign diseases. Materials and methods: Forty-one patients aged 34 to 56 years were enrolled for abdominal hysterectomy - 20 as the case group (hysterectomy with UM application) and 21 as the control group (conventional hysterectomy). In the case group, UM was used after uterus artery ligation during TAH. The control group underwent traditional TAH. Results: The mean operation time was significantly less in TAH with UM compared to traditional TAH (90.23 ± 10.54 minutes vs. 140.5 ± 16.61 minutes; p-value<0.001). The mean decline between preoperative and 12-hour postoperative hemoglobin was 0.74 ± 0.23 mg/dL in the TAH with UM group and 1.65± 1.02 mg/dL in the traditional TAH group (p-value<0.001). Also, no difference was detected in intra- and post-operative complications. Conclusion: The current study showed that, using UM is beneficial in total abdominal hysterectomy by decreasing the operative time and blood loss.